Deformation Monitoring Of Marwat-Khisor Ranges, Pakistan Using Interferometric Synthetic Aperture Radar - Fadzil, Fakhrul Hazwan Ahmad (2023)
Main Frontal Thrust (MFT) represents the southern boundary of Himalaya, which accommodated the current orogeny of Eurasian-Indian tectonic plate’s convergence. The deformation pattern and structural style of MFT are crucial for understanding the tectonic activities. A chain of fold-and-thrust (FAT) belts (Salt-Trans Indus Ranges) are identified as the MFT in the western Himalaya. The Salt Range had propagated southward at an average rate of 5-10 mm/year in the influence of salt tectonics. Although the Trans Indus Ranges had indicated an active Quaternary tectonics, the fault slip rate and direction was unknown. This study focused on the Marwat-Khisor Ranges (a segment of Trans Indus Ranges), the youngest part of the MFT in the western Himalaya. Remote sensing techniques such as Interferometric Synthetic Aperture Radar (InSAR) Permanent Scatterer (PS), lineament extraction and geometric analysis of salient were implemented to investigate the deformation mechanisms and active tectonics. InSAR processing of 80 Sentinel-1 images showed the Marwat-Khisor Ranges were uplifting in the satellite line-of-sight at an average rate of 3-7 mm/year dated from 18th October 2014 to 18th June 2019. The Marwat-Khisor Ranges are the hanging wall sequence that ramped up section above the partially emergent Khisor Thrust where surface uplift is expected.